From Play to Practice: Designing the Menararia Board Game for Promoting Clean and Healthy Living Behavior Among School-Aged Children - Taufan Asrisyah Ode; Ruri Andesmana; Sania Salsabila (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Clean and Healthy Living Behavior in schools serves as a foundational step toward cultivating healthy and high-quality human resources for national development. This study aimed to develop a health promotion medium in the form of a board game called Menararia, designed to enhance knowledge and engagement among school-aged children. This research employed a qualitative research and development (R&D) design. Informants were selected purposively and consisted of three experts (a media specialist, a public health expert, and a practitioner) and three elementary school students. Data were collected through direct observation and in-depth interviews. The development process comprised strategic design, media development, and initial testing. During the strategic design phase, the team defined communication objectives using the SMART framework, launched a school-based improvement program called ARSHAT (Anak Bersih, Sehat, Kuat or Clean, Healthy, and Strong Children), identified key implementation partners (e.g., Jember Health Office, Semboro Health Center, and UNICEF Indonesia), and established an implementation timeline (March-May 2023). The development phase included creating educational materials based on eight indicators, designing game components (board, cards, and rules), and producing visual elements with consistent use of blue, white, and gray color schemes and child-friendly typography (Poppins, PhagsPa, Arial). Experts found the game largely appropriate but recommended minor adjustments. The Menararia board game shows strong potential as a health communication medium to promote Clean and Healthy Living Behavior among children. Initial feedback suggests it is engaging and contextually relevant, though minor content revisions are needed to optimize its effectiveness. Keywords: Clean and Healthy Living Behavior, Board Game, School-Aged Children, Health Promotion, Educational Media